On the Effect of Applying the Task Clustering for Identical Processor Utilization to Heterogeneous Systems - Kanemitsu, Hidehiro; Lee, Gilhyon; Nakazato, Hidenori; Hoshiai, Takashige; Urano, Yoshiyori (IntechOpen, 2012)
None